2016
DOI: 10.1007/s10948-016-3619-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Elastic, and Electronic Properties of Newly Discovered Li2PtSi3 Superconductor: Effect of Transition Metals

Abstract: First-principles calculations within the density functional theory (DFT) with GGA-PBE exchangecorrelation scheme have been employed to predict the structural, the elastic and the electronic properties of newly discovered lithium silicide superconductor, Li 2 PtSi 3 , for the first time. All the theoretical results are compared with those calculated recently for isostructural Li 2 IrSi 3 . The present study sheds light on the effect of replacement of transition metal element Ir with Pt on different mechanical, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…The electron-phonon interaction potential appears to be much stronger in ScIrP compared to ScRhP. It is quite interesting to note that the superconducting state properties of these two ternary phosphides are almost identical to those of recently discovered hexagonal ternary silicide compounds, Li 2 IrSi 3 and Li 2 PtSi 3 [45,46]…”
supporting
confidence: 56%
“…The electron-phonon interaction potential appears to be much stronger in ScIrP compared to ScRhP. It is quite interesting to note that the superconducting state properties of these two ternary phosphides are almost identical to those of recently discovered hexagonal ternary silicide compounds, Li 2 IrSi 3 and Li 2 PtSi 3 [45,46]…”
supporting
confidence: 56%
“…In this investigation we have concentrated on the bulk electronic, optical and mechanical properties of orthorhombic MoTe 2 . Variety of prior studies on diverse class of materials showed that [26][27][28][29][30], as far as optimization of the cell structure, bulk elastic constants, bonding and bulk optical properties are concerned, SOC only has a minimal effect. Within the bulk electronic band structure, SOC mainly reveals itself in split bands with splitting energy of the order of tens of meV.…”
Section: Methods and Crystal Structurementioning
confidence: 99%
“…The large TDOS is a sign of high metallicity the compound. The TDOS at the Fermi level is quite high compared to some other recently discovered ternary superconducting compounds [52,53]. This may be responsible for the higher superconducting transition temperature in LaRu 2 As 2 , compared to, for example, in ternary silicides [54].…”
Section: Band Structure and Density Of Statesmentioning
confidence: 90%